Hysteretic mechanical–informational modeling of bolted steel frame connections - Kim, JunHee; Ghaboussi, Jamshid; Elnashai, Amr S. (Engineering structures, 2012)
► We proposed a novel modeling method, hybrid mechanical–informational modeling (HMIM). ► We modeled complex hysteretic behavior of bolted connections using the HMIM framework. ► The pinching effects resulting from slip and bolthole ovalization are suitable for informational modeling. ► The moment–rotation curve of the hybrid model is validated with that of the experimental test. The behavior of bolted beam-to-column connections in steel and composite frames has a significant effect on their structural response to strong ground motion. Their hysteretic response exhibits highly inelastic characteristics and continuous variation in stiffness, strength and ductility, hence they influence both supply and demand. Therefore, accurate hysteretic models of bolted connections are essential to accurate seismic assessment and design. In this paper, a novel hybrid modeling approach is proposed to represent the complex hysteretic behavior of bolted connections when frames are subject to strong ground motion from earthquakes. The basic premise of the proposed approach is that not all features of connection response are amenable to mechanical modeling; hence consideration of information-based alternatives is warranted. In the hybrid mechanical–informational modeling (HMIM) framework, the conventional mechanical model is complemented by information-based model components. The informational components represent aspects of the behavior that the mechanical model leaves out. The performance of HMIM is illustrated through applications to flange-plate connections, which exhibit highly pinched hysteretic behavior.